Keeping the Pulse of Heritage Awareness in Ankara: Two Historic Sites, Two Interventions - ECE KUMKALE ACIKGOZ (Journal of Contemporary Urban Affairs, 2019)
How heritage is preserved and transmitted to the future is heavily dependent on the responsible awareness of its local society. Transformations in a historic urban landscape (HUL) are intervening into its collective memory, affecting its social sustainability and resilience. This paper considers two of these cases from the historic district of Ankara, namely Hacibayram Square and Hergelen Square, to see whether the demographic changes in the society has a similar consequence on the public awareness of the historicity and heritage values of their sites. The first case, which is a cult site of heritage, history, and religion, was previously studied. This paper explains the study for the second case, Hergelen (itfaiye) Square with a more recent historical significance, and interprets the outcomes of the two studies tieh their differing and common aspects. Hergelen Square has been exposed to a series of demolitions, two of which are the foci of this work: the Bank of Municipalities building, a heritage monument from the early republican era of Turkey, and Otto Herbert Hajek’s sculpture. The questionnaire outcomes of both independent surveys demonstrated that as the educational level of the participants decreased the admiration for the transformative interventions increased. However, being identified with different priorities and functions, the case of Hergelen Square, when considered with its past and former interventions that it has been exhausted to, implicated further insights about the problem of integrity of the HUL of Ankara.